2005
DOI: 10.1542/peds.2004-1726
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Racial and Ethnic Disparities After Enrollment in the State Children's Health Insurance Program

Abstract: ABSTRACT. Background. Racial/ethnic disparities are associated with lack of health insurance. Although the State Children's Health Insurance Program (SCHIP) provides health insurance to low-income children, many of whom are members of racial/ethnic minority groups, little is known about whether SCHIP affects racial/ethnic disparities among children who enroll.Objectives. The objectives of this study were to (1) describe demographic characteristics and previous health insurance experiences of SCHIP enrollees by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 65 publications
1
63
0
Order By: Relevance
“…Encouragingly, no significant differences were found by race over the study period. One possible explanation is that enrollment in the New York State Children's Health Insurance Program, which has shown to reduce preexisting racial/ethnic disparities in health-care access, and improve continuity and quality of care for enrollees, 53 may have contributed to the larger number of minority subjects in this trial and nonsignificant differences. Nationally, as pediatric allo-SCT is increasingly being used as curative therapy and access to such programs improves, the implications of this finding will be important for future comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, no significant differences were found by race over the study period. One possible explanation is that enrollment in the New York State Children's Health Insurance Program, which has shown to reduce preexisting racial/ethnic disparities in health-care access, and improve continuity and quality of care for enrollees, 53 may have contributed to the larger number of minority subjects in this trial and nonsignificant differences. Nationally, as pediatric allo-SCT is increasingly being used as curative therapy and access to such programs improves, the implications of this finding will be important for future comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…125 In a study in a community sample of parents and adolescents (N = 775), maternal depression and paternal depression were both significantly associated with depression in adolescents. 126 A meta-analysis of fathers' mental health and child psychopathology found that paternal depression was significantly correlated with child and adolescent internalizing symptoms. 127 Other studies have shown that father involvement is associated with a decrease in externalizing behavior problems.…”
Section: Influence Of Fathers' Mental and Physical Well-being On Chilmentioning
confidence: 99%
“…Blacks have been shown to experience higher mortality, less access to care, higher risk of renal disease progression, fewer referrals for renal transplantation, and shorter renal allograft survival than Whites (1)(2)(3)(4)(5). Some programs aimed at enhancing access to care have shown improvements in this health gap (6,7). The common theme of such interventions is the amelioration of financial, socioeconomic, and other (occasionally including transportation) barriers to access and care.…”
mentioning
confidence: 99%